Gaussian Pulse-Based Two-Threshold Parallel Scaling Tone Reservation for PAPR Reduction of OFDM Signals - Lei Guan; Anding Zhu (International Journal of Digital Multimedia Broadcasting)
Tone Reservation (TR) is a technique proposed to combat the high Peak-to-Average Power Ratio (PAPR) problem of Orthogonal Frequency Division Multiplexing (OFDM) signals. However conventional TR suffers from high computational cost due to the difficulties in finding an effective cancellation signal in the time domain by using only a few tones in the frequency domain. It also suffers from a high cost of hardware implementation and long handling time delay issues due to the need to conduct multiple iterations to cancel multiple high signal peaks. In this paper, we propose an efficient approach, called two-threshold parallel scaling, for implementing a previously proposed Gaussian pulse-based Tone Reservation algorithm. Compared to conventional approaches, this technique significantly reduces the hardware implementation complexity and cost, while also reducing signal processing time delay by using just two iterations. Experimental results show that the proposed technique can effectively reduce the PAPR of OFDM signals with only a very small number of reserved tones and with limited usage of hardware resources. This technique is suitable for any OFDM-based communication systems, especially for Digital Video Broadcasting (DVB) systems employing large IFFT/FFT transforms.